Mobile Application and Web 2.0 as an E-Participation Mechanism: A Literature Analysis - Manaf, Halimah Abdul; Man, Mohamad Nur Salam (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Every democratic government always in their goals in achieving inclusiveness in every decision-making process which will prevail in their efforts achieving the full principle of democracy, transparent, accountable, and good governance. Hence, e-participation has profoundly become one set of tools in bridging digital divide between people and their governments (C2G), governments and other government organisations (G2G), government and people (G2C), government and employees (G2E), and government and corporation (G2B) through the utilization advancement of information and communication technology (ICT). In regards to this, the mobile application and Web 2.0 system are often flagged for its potential in improving public participation which intended to improve the current lagging public services and to establish relationships between government and citizens based on virtual information sharing and public debate. Insight of this, does mobile application and Web 2.0 able to deliberately enhance e-participation in everydimension? Every democratic government always in their goals in achieving inclusiveness in every decision-making process which will prevail in their efforts achieving the full principle of democracy, transparent, accountable, and good governance. Hence, e-participation has profoundly become one set of tools in bridging digital divide between people and their governments (C2G), governments and other government organisations (G2G), government and people (G2C), government and employees (G2E), and government and corporation (G2B) through the utilization advancement of information and communication technology (ICT). In regards to this, the mobile application and Web 2.0 system are often flagged for its potential in improving public participation which intended to improve the current lagging public services and to establish relationships between government and citizens based on virtual information sharing and public debate. Insight of this, does mobile application and Web 2.0 able to deliberately enhance e-participation in everydimension?